Structural insights into how Cas9 targets nucleosomes - Reina Nagamura; Tomoya Kujirai; Junko Kato; Yutaro Shuto; Tsukasa Kusakizako; Hisato Hirano; Masaki Endo; Seiichi Toki; Hiroaki Saika; Hitoshi Kurumizaka; Osamu Nureki (Nature Communications)
Abstract The CRISPR-associated endonuclease Cas9 derived from prokaryotes is used as a genome editing, which targets specific genomic loci by single guide RNAs (sgRNAs). The eukaryotes, the target of genome editing, store their genome DNA in chromatin, in which the nucleosome is a basic unit. Despite previous structural analyses focusing on Cas9 cleaving free DNA, structural insights into Cas9 targeting of DNA within nucleosomes are limited, leading to uncertainties in understanding how Cas9 operates in the eukaryotic genome. In the present study, we perform native-polyacrylamide gel electrophoresis (PAGE)  analyses and find that Cas9 targets the linker DNA and the entry-exit DNA region of the nucleosome but not the DNA tightly wrapped around the histone octamer. We further determine cryo-electron microscopy (cryo-EM) structure of the Cas9-sgRNA-nucleosome ternary complex that targets linker DNA in nucleosomes. The structure suggests interactions between Cas9 and nucleosomes at multiple sites. Mutants that reduce the interaction between nucleosomal DNA and Cas9 improve nucleosomal DNA cleavage activity in vitro, although inhibition by the interaction between Cas9 and nucleosomes is limited in vivo. These findings will contribute to the development of novel genome editing tools in chromatin.